Beyond Technocratic Quality Assurance: Humanizing Digital Governance through South Sumatran Ethnopedagogy - Ismatul Kholilah; Erik Pebrikarlepi; Alifah Ratna Irtiyah (PT. Student Rihlah Indonesia, 2026)
Digital governance has become a fundamental component of quality assurance in higher education within the era of Quality 4.0. However, its implementation frequently emphasizes administrative compliance and data-driven performance indicators, thereby diminishing the humanistic dimension of quality assurance, particularly in Islamic higher education institutions. This study aims to reconstruct a humanistic digital quality governance framework at Ittifaqiah Al-Qur'an University (UQI) Indralaya through the integration of the ethnopedagogical values of South Sumatra and pesantren spirituality. The study employed a qualitative approach using a conceptual-philosophical design based on library research. Data were analyzed interpretively through a review of the literature on digital governance, Quality 4.0, ethnopedagogy, Simbur Cahaya, and pesantren values. The findings indicate that the PPEPP cycle can be reconstructed by integrating Simbur Cahaya as the ethical foundation of quality assurance, Saling Setiti as the professional ethic guiding quality management, and Saling Setuhu as the basis for dialogic and collaborative evaluation. The novelty of this study lies in the development of a conceptual framework that integrates the ethnopedagogical values of South Sumatra and pesantren spirituality into digital quality governance. These findings provide implications for the development of more contextual, humanistic, and locally grounded policies for the Internal Quality Assurance System (SPMI) and higher education accreditation.